Matrix board - Ismadi, Muhammad Izzul Haiqal; Khalid, Ahmad Aqil; Md Ismail, Muhammad Fakhrulradzi Haiqal; Suhaimi, Muhammad Nasrullah; Efendi, Malik (Universiti Teknologi MARA, Kedah, 2023)
Matrix Board is produced to increase the interest of students in learning the subject of matric and make learning matric more interesting. It also reduces dependence on the use of calculators and improves exam performance in mathematics subjects. The results of the Pre and Post Tests show an increase in student achievement in answering Matrix questions among 50 form 5 students. The increase in the number of students who obtained higher scores in the Post test shows the effectiveness of using the Matrix Board. The findings of the survey show that the Matrix Board is able to increase students' interest, provide a positive effect and impact and it is more effective in helping to attract students' interest. It is hoped that the Matrix Board can be used by other school students in mastering the matrix topic. In addition, Matrix Board has the potential to be marketed as a learning stimulant as well as a board game that has a positive impact on student learning.